2015
DOI: 10.1016/j.pupt.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Role of the dorsal medulla in the neurogenesis of airway protection

Abstract: The dorsal medulla encompassing the nucleus of the tractus solitarius (NTS) and surrounding reticular formation (RF) has an important role in processing sensory information from the upper and lower airways for the generation and control of airway protective behaviors. These behaviors, such as cough and swallow, historically have been studied in isolation. However, recent information indicates that these and other airway protective behaviors are coordinated to minimize risk of aspiration. The dorsal medullary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…This obviously implies that NTS ascending projections provide synaptic interactions with neurons responsible for respiratory pattern formation Mutolo Respiratory Physiology & Neurobiology 243 (2017) 60-76 (see Jones et al, 2016 also for further Refs.). All these results support the notion that the cNTS is not a mere relay station, but plays more extensive functions in cough motor pattern generation and, in addition, that it is an important location of cough-gating neurons (see Haji et al, 2013;Bolser et al, 2015;Pitts et al, 2016; also for further Refs.). However, it cannot be at present completely excluded that other respiration-related regions, such as the raphe nuclei, the cVRG or the BötC, may contribute to the cough-gating mechanism.…”
Section: Cough-gating Mechanismsupporting
confidence: 79%
See 1 more Smart Citation
“…This obviously implies that NTS ascending projections provide synaptic interactions with neurons responsible for respiratory pattern formation Mutolo Respiratory Physiology & Neurobiology 243 (2017) 60-76 (see Jones et al, 2016 also for further Refs.). All these results support the notion that the cNTS is not a mere relay station, but plays more extensive functions in cough motor pattern generation and, in addition, that it is an important location of cough-gating neurons (see Haji et al, 2013;Bolser et al, 2015;Pitts et al, 2016; also for further Refs.). However, it cannot be at present completely excluded that other respiration-related regions, such as the raphe nuclei, the cVRG or the BötC, may contribute to the cough-gating mechanism.…”
Section: Cough-gating Mechanismsupporting
confidence: 79%
“…On the other hand, an impairment of airway protective reflexes, including cough and swallowing, in some neurodegenerative diseases such as Parkinsonism, Alzheimer's disease and fronto-temporal dementia, or following ictus could lead to high risk of aspiration and consequent life-threatening conditions (e.g. Dicpinigaitis et al, 2014;Dutschmann et al, 2014;Bolser et al, 2015;Pitts et al, 2016;Cinelli et al, 2016). Admittedly, studies on animal models of chronic cough or neurodegenerative diseases could be more appropriate to disclose novel therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Distinct pattern generators have been proposed for a variety of motor behaviors involving the DIAm, including coughing (9,67,78), swallowing (9,48), and sighing (57). We previously showed that the recruitment order during spontaneous breathing was preserved even during sighs and airway occlusion (77), suggesting that these behaviors likely are realized through the pattern generator for breathing.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of prior intubation on the CPF during reflexive cough is a topic that needs assessment in future studies. A final point is that the cough center is at the brainstem level, 33 and therefore patients with infratentorial lesions affecting this center would show more compromised cough function. 14 However, our results were unable to demonstrate whether CPF was more limited in individuals with infratentorial lesions than in individuals with supratentorial lesions.…”
Section: Discussionmentioning
confidence: 99%